Efinaconazole topical solution 10%: Formulation and efficacy assessment in the treatment of toenail onychomycosis. Issue 5 (6th March 2020) - Naeimifar, Atefeh; Samadi, Aniseh; Ahmad Nasrollahi, Saman; Fattahi, Azam; Ghasemi, Zeinab; Azizzadeh‐Roodpishi, Shadi; Malakooti, Shiva; Ehsani, Amir Hooshang; Firooz, Alireza; Dowlatiy, Yahya
Summary: Background: Efinaconazole is non‐lacquer‐based with a low surface tension that efficiently targets delivery of active ingredient into the nail and nail bed. Objectives: To develop an optimal, stable formulation of efinaconazole topical solution 10% (ETS10). Methods: We evaluated the safety and efficacy of ETS10 on 10 Iranian participants in a pilot, single‐group and before‐after clinical study, for up to 8 weeks in onychomycosis. Results: The study showed reasonable results concerning the short period of treatment. During the period of storage, the formulation showed no variation in colour, odour and pH. The average pH at initial, 1st, 6th and 12th months was 4.65, 4.64, 4.65 and 4.64, respectively. The assay of an active pharmaceutical ingredient in the formulation was desired over the whole period. This indicates that antimicrobial activity has been adequate and efficient. A significant decrease in Investigator Global Assessment (IGA) of the target toenails was also defined as the efficacy endpoint. The median score for IGA at baseline visit was 3 out of 5 which decreased to 2 out of 5 and the decrease was statistically significant. Conclusion: The study clarifies the new efficacy of ETS10 in subjects with onychomycosis and passed the safety study successfully. These properties may develop the potentiality of ETS10 as a good treatment option for patients with onychomycosis.